Word Wall Strategy: Does It Have an Effect on Students’ English Tenses Mastery? - Zen, Akbar Ibnu; Rohmana, Rohmana (Universitas Halu Oleo, 2021)
This research is conducted to describe whether or not Word Wall Strategy has a significant effect on students’ English tenses mastery at grade VIII of Junior High School 1 Kendari. It focused on two tenses, namely simple present tense and simple past tense. The population of this research was grade VIII students of Junior High School 1 Kendari consisting of ten classes, while the subject of this research was class VIII6 which consisted of 34 students. This research was conducted in pre-experimental research design. The data of this research were collected by giving pre-test and post-test to students. They were calculated through SPSS 16.00 version and analyzed by using descriptive analysis and inferential statistics. As for testing the hypothesis, the researcher uses paired sample t-test.The result showed that there was an improvement of the students’ English tenses mastery. It can be seen on the mean score of post-test which was 69.55, while the mean score of pre-test was 32.88. In order to prove the hypothesis, the researcher took the conclusion by comparing between the value of Sig (2 tailed) with the significance α value. It showed that the value of Sig (2 tailed) was 0.000 while the significance α value was 0.05. Therefore, it can be concluded that the value of Sig (2 tailed) was lower than the significance α value (0.000 < 0.05). It means that there was a significant effect of Word Wall Strategy on students’ English tenses mastery at grade VIII of Junior High School 1 Kendari.